A rare case of anomalous origin of the left main coronary artery in an adult patient - Dionne, Pierre O (BioMed Central, 2013)
Anomalous origin of left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital anomaly that causes a left-to-right shunt via the coronary system, resulting in coronary steal. We report an unusual case of a healthy 48 years-old patient presenting with dyspnea on exertion and mild chest pain who underwent surgical correction of this rare anomaly. Multiple procedures have been proposed in adults with ALCAPA. Although re-implantation of the left main coronary artery (LMCA) to the aorta remains the most physiological correction for this anomaly, the combination of LMCA ligation and coronary artery bypass grafting provides a dual coronary flow system and is preferable when re-implantation is impossible.